Answer:
Solving 14t-3t we get 22 and 3t-14t we get -22
So, 14t-3t is not equivalent to 3t-14t.
Step-by-step explanation:
We need to explain weather 14t-3t is equivalent to 3t-14t. Support your sender by evaluating the expression for t=2.
Equivalent expressions are those that have same values for any value of variable substituted.
Now, We check if our expressions are equivalent, by evaluating the expression for t=2.
If they are equivalent, they would have same result after evaluation.
First, put t=2 into 14t-3t
![14t-3t\\Put\:t=2\\=14(2)-3(2)\\=28-6\\=22](https://img.qammunity.org/2022/formulas/mathematics/high-school/z53jlykpw7hbdbvz4kr6k7cjtd8hutz8gi.png)
Now put t=2, into 3t-14t
![3t-14t\\Put\:t=2\\=3(2)-14(2)\\=6-28\\=-22\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/vi2ztyzicq70pn3kb6d0q60iz2cvo7lyb4.png)
For solving 14t-3t we get 22 and 3t-14t we get -22
So, 14t-3t is not equivalent to 3t-14t.